Beak morphometrics and line analysis for accurate sex determination in juvenile Lovebird (Agapornis fischeri) - YENI DHAMAYANTI; ZALFA HIFNIE WAHYUNITA; FEDIK ABDUL RANTAM; MASLICHAH MAFRUCHATI; HANA ELIYANI; SOEHARSONO SOEHARSONO; GRACIA ANGELINA HENDARTI; TANTRI DYAH WHIDI PALUPI; KURNIA NISA KINASIH; ZULFI NUR AMRINA ROSYADA; AISYAH NIKMATUZ ZAHRO; SALIPUDIN TASIL MASLAMAMA; MUHAMMAD THOHAWI ELZIYAD PURNAMA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dhamayanti Y, Wahyunita ZH, Rantam FA, Mafruchati M, Eliyani H, Soeharsono, Hendarti GA, Palupi TDW, Kinasih KN, Rosyada ZNA, Zahro AN, Maslamama ST, Purnama MTE. 2025. Beak morphometrics and line analysis for accurate sex determination in juvenile Lovebird (Agapornis fischeri). Biodiversitas 26: 14-21. Particular consideration must be dedicated to the welfare of birds as pets and trade animals in the context of biodiversity. Lovebirds (Agapornis fischeri (Reichenow, 1887)) are well-liked birds all around the world because of their lovely chirping sound and diverse ornaments. This study aimed to investigate the precision of differentiating between male and female juvenile Fischer lovebirds through beak morphometry and beak line analysis. A total of 54 Fischer's lovebirds, 27 males and 27 females aged 4, 5, and 6 months, were meticulously investigated in this study. The beak length, width, and depth were measured using a caliper with utmost care. The beak angle and beak line pattern were measured using the ImageJ application. Data was analyzed using MANOVA and crosstab in SPSS v.26. This study reported no significant difference in morphometric beak length, width, and depth in lovebirds aged 4, 5, and 6 months. In addition, this study reported differences in morphometry of the beak angle in Lovebirds aged 4, 5, and 6 months. The comparison of the interaction between sex and the line pattern to the eyes of Fischer lovebirds at the age of 4 and 6 months reported insignificant results, and at the age of 5 months, showed significant results. In conclusion, starting at 4 months of age, an alternative method for determining the sex of Fischer lovebirds is the morphometric technique of measuring the beak angle.